On structures in hypergraphs of models of a theory - Kulpeshov, B.Sh.; Sudoplatov, S.V. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
Hypergraphs of models of a theory are derived objects allowing toobtain an essential structural information about both giventheories and related semantic objects including graph ones. In the present paper we define and study structural properties of hypergraphs of modelsof a theory including lattice ones. Characterizations for thelattice properties of hypergraphs of models of a theory, as wellas for structures on sets of isomorphism types of models of atheory, are given.
Теория модельдерінің гиперграфтарындағы құрылымдар туралы
О структурах в гиперграфах моделей теории
Keywords: hypergraph of models; elementary theory; elementarily substructural set; lattice structure